1999
DOI: 10.1021/ja981742j
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lived Photoinduced Charge Separation and Redox-Type Photochromism on Mesoporous Oxide Films Sensitized by Molecular Dyads

Abstract: The photoinduced charge separation in three different assemblies composed of an electron donor D and a chromophore sensitizer S adsorbed on nanocrystalline TiO2 films (D−S|TiO2) was investigated. In all of the systems, the sensitizer was a ruthenium(II) bis-terpyridine complex anchored to the semiconductor surface by a phosphonate group. In two of the assemblies, the donor was a 4-(N,N-di-p-anisylamino) phenyl group linked to the 4‘ position of the terpyridine, either directly (dyad D1−S) or via a benzyl ether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
191
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(198 citation statements)
references
References 36 publications
7
191
0
Order By: Relevance
“…11 In our study correlation between hole transport and hole lifetime is observed for samples fabricated on glass substrates or including a TiO2 compact layer covering the FTO contact indicating that hole transfer to electrons in FTO does not contribute to observed trend in recombination kinetics.…”
Section: The Effect Of Disorder On Recombinationmentioning
confidence: 59%
See 1 more Smart Citation
“…11 In our study correlation between hole transport and hole lifetime is observed for samples fabricated on glass substrates or including a TiO2 compact layer covering the FTO contact indicating that hole transfer to electrons in FTO does not contribute to observed trend in recombination kinetics.…”
Section: The Effect Of Disorder On Recombinationmentioning
confidence: 59%
“…The results presented evidence for systems showing longer lifetimes due to reaction limitations as opposed to electron transport limitation. 8,9,10,11 Thus, tuning surface properties 12,13 and modifying the dye chemical structure 9 have been emphasized as routes to minimise electron-dye recombination. On the other hand, other reports showed unchanged recombination dynamics upon change in dye chemical structure, suggesting that diffusion limited encounter between electrons and holes represents the rate limiting process in some systems.…”
Section: Introductionmentioning
confidence: 99%
“…The observed suppression of the carriers recombination is attributed to an increase in the physical separation between the dye cation and the metal oxide surface. Bonhôte and coworkers have studied the charge recombination process in a series of Ru dyes connected with triphenylamine (Bonhôte et al 1999). The lifetime of injected electrons in TiO 2 is enhanced by a significant factor of 100 times after the incorporation of those units in their model system (without I − /I 3 − redox couples so that the carrier recombination mostly occurs between the oxidized dye and the injected electrons).…”
Section: The Task To Reduce Charge Recombination Between the Oxidizedmentioning
confidence: 99%
“…The derivatization of nanocrystalline films with different types of molecular monolayers led to, in addition to solar cells and electrochromic devices, to elaborate sensors, 20 photoelectrocatalytic, 21 electroluminescent 22 and photoelectrochromic devices. 23 The common principle of efficiency in these devices lies on fast interfacial electron transfer between the nanocrystalline material and the adsorbed modifier as well as on the high surface area of the substrate that amplifies optical phenomena by two or three orders of magnitude. The general principle of the electrochromism of a molecular monolayer adsorbed on TiO 2 is depicted in Figure 2, electrons are injected from the conducting substrate into the conduction band of the semiconductor and from there, reduce the adsorbed organic chromophore.…”
Section: Electrochromic Nanomaterialsmentioning
confidence: 99%